Lipoproteins in Gram-Positive Bacteria: Abundance, Function, Fitness - Nguyen, Minh-Thu; Matsuo, Miki; Niemann, Silke; Herrmann, Mathias; Götz, Friedrich (Frontiers in Microbiology, 2020)
When one thinks of the Gram+ cell wall, the peptidoglycan (PG) scaffold in particular comes to mind. However, the cell wall also consists of many other components, for example those that are covalently linked to the PG: the wall teichoic acid and the cell wall proteins tethered by the sortase. In addition, there are completely different molecules that are anchored in the cytoplasmic membrane and span the cell wall. These are lipoteichoic acids and bacterial lipoproteins (Lpp). The latter are in the focus of this review. Lpp are present in almost all bacteria. They fulfil a wealth of different tasks. They represent the window to the outside world by recognizing nutrients and incorporating them into the bacterial cell via special transport systems. Furthermore, they perform very diverse and special tasks such as acting as chaperonin, as cyclomodulin, contributing to invasion of host cells or uptake of plasmids via conjugation. All these functions are taken over by the protein part. Nevertheless, the lipid part of the Lpp plays an as important role as the protein part. It is the released lipoproteins and derived lipopeptides that massively modulate our immune system and ultimately play an important role in immune tolerance or non-tolerance. All these varied activities of the Lpp are considered in this review article.